Penyelenggaraan Pendidikan Inklusif Berbasis Budaya Local - Minan Ainur Fatah; Praptiwi Nur Auliya Hidayah (Reslaj: Religion Education Social Laa Roiba Journal, 2026)
Education serves as the foundation of the learning process and plays an essential role in achieving educational goals, including the implementation of inclusive learning. The application of inclusive education cannot rely solely on policies and adequate facilities; it also requires approaches that are relevant to students’ lives, including the integration of local culture within their environment. This study employs a qualitative method using a library research approach, focusing on collecting, reviewing, and analyzing various literature sources related to the topic. Inclusive education emphasizes the fulfillment of every learner’s right to receive equal educational services without discrimination. Its implementation requires the readiness of teachers, schools, parents, and the social environment. Integrating local cultural values into learning strengthens character education through norms, traditions, and wisdom that make the learning process more contextual and meaningful. The synergy between inclusive education and local wisdom shares the same goal: to shape students with strong character, respect for diversity, and the ability to live harmoniously in a pluralistic society. By combining these two approaches, character formation becomes more effective and culturally relevant.